Correlates of condom use among school-going Thai adolescents: the critical role of bullying victimizations - Omid Dadras (BMC Psychiatry)
Abstract Background Adolescents face numerous challenges that influence their sexual behaviors. Among these, bullying victimization is a critical yet understudied factor that may impact engagement in unprotected sex. This study investigated the correlates of condom use among school-going Thai adolescents, with a main focus on bullying victimization. Methods This study is a secondary analysis of the Global School-based Student Health Survey (GSHS) conducted in 2021 among a nationally representative sample of students in grades 7–12 in Thailand. The analysis included all the sexually active students with condom use in the last sex as the main outcome variable. Bivariate binary logistic regression analysis was used to examine the odds of using condom across various explanatory variables. Additional adjusted logistic regression models were constructed to examine the association between bullying experiences and condom use while controlling for the potential confounding effect of other explanatory variables. Results Among sexually active participants, 416 (69%) reported using condoms in their last sex and more than half of them reported bullying experiences. Besides bullying, this study identifies several factors such as older age (< 14) and higher grades that were associated with lower use of condoms. Additionally, other psychosocial factors such as suicidal ideation and attempts as well as physical violence, and lack of close friends decrease the odds of condom use. Substance use, particularly marijuana and amphetamine/methamphetamine, was also associated with lower condom use. Although all types of bullying experiences were associated with lower condom use in bivariate analyses, the association remained significant only for bullying at school in the adjusted model (AOR = 0.39, 95% CI: 0.18–0.86). Conclusion The findings emphasize a holistic approach to addressing bullying, particularly within schools, and promoting protected sexual behaviors among school-going adolescents through early anti-bullying interventions and incorporating tailored sex education into school curricula, and at Thai schools.